Killing the model minority stereotype : Asian American counterstories and complicity - Hartlep, Nicholas Daniel; Porfilio, Bradley J. (Emerald Publishing Limited : Information Age Publishing, Inc., 2015)
Killing the Model Minority Stereotype comprehensively explores the complex permutations of the Asian model minority myth, exposing the ways in which stereotypes of Asian/Americans operate in the service of racism. Chapters include counter-narratives, critical analyses, and transnational perspectives. This volume connects to overarching projects of decolonization, which social justice educators and practitioners will find useful for understanding how the model minority myth functions to uphold white supremacy and how complicity has a damaging impact in its perpetuation. The book adds a timely contribution to the model minority discourse.